The Effectiveness of Teaching Bridges Program in Developing E-blended Learning Strategies in Light of Corona Pandemic from Principals Light of View - Al-Hawamleh, Fairouz Mustafa Jamil (Journal of Educational and Psychological Sciences, 2021)
This Study aimed to identify the degree of effectiveness of Teaching Bridges program in developing E-Blended learning strategies in light of Corona pandemic from principals perspective in Al-Tafeilh directorate, and to determine the effect of some variables (sex, and years of experience), the researcher used the Descriptive approaches, study population consisted of all principal in Al- Tafeilh directorate (88) Female and male, the sample consist from (45) Female and (28)male, chosen randomly, to collect data Questioner used, which consisted (25) paragraph, the result of SPSS analysis shown that the degree of effectiveness of Teaching Bridges program in developing E-Blended learning strategies in light of Corona pandemic from principals perspective in Al-Tafeilh directorate was High, The finding also showed there is no statistically significant differences at (α≤0.05) refers to principal sex (male and female) in addition there were statistically significant differences between the principals years of experience in favor of (10 years and more).
Keywords: Teaching Bridges Program; E-blended Learning; Corona Pandemic